2017
DOI: 10.1007/s12094-017-1745-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of neoadjuvant chemotherapy response using diffuse optical spectroscopy in breast cancer

Abstract: PurposeNear-infrared diffuse optical spectroscopy (DOS) has been recently used to predict neoadjuvant chemotherapy response (NAC). In the present study, we explore the change in blood-oxygen content using DOS to predict NAC response against breast cancer.Materials and methodsA total of 20 patients were enrolled and underwent DOS scan with blood-oxygen detection before each treatment cycle. The first DOS scan was performed before NAC treatment (pretreatment), and subsequent scans were performed after each NAC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…In this study, we demonstrated that DOTBIS measured features change in accordance with pCR status after 2-3 weeks under NAC, and when combined to HER2 status could be a predictive factor for pCR. Our findings complement and extend previous smaller studies conducted from 2007 to 2018 (8,9,(11)(12)(13)(14)(15)(16)(17)(18)20,21). Giving our larger sample size (n = 89), and multiple imaging time points, we were also able to detect differences within the breast tumor subtypes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we demonstrated that DOTBIS measured features change in accordance with pCR status after 2-3 weeks under NAC, and when combined to HER2 status could be a predictive factor for pCR. Our findings complement and extend previous smaller studies conducted from 2007 to 2018 (8,9,(11)(12)(13)(14)(15)(16)(17)(18)20,21). Giving our larger sample size (n = 89), and multiple imaging time points, we were also able to detect differences within the breast tumor subtypes.…”
Section: Discussionsupporting
confidence: 85%
“…The present study adds to the body of evidence reported for diffuse optical imaging methods applied to breast cancer treatment response. Our findings complement and extend previous smaller studies conducted from 2007 to 2018 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) which have identified optical-based imaging markers correlated to pCR at different time points throughout NAC. In a metaanalysis study (19), Liu et al demonstrated that DOT has clinically acceptable predictive values.…”
Section: Introductionsupporting
confidence: 89%
“…Several studies indicate that the effect of chemotherapy can be measured with optical technologies. [12][13][14] The fact that the optical properties of tissue alter due to chemotherapy is not surprising, as effects of chemotherapy are seen in tumor tissue [15][16][17] as well as in healthy breast tissue. [16][17][18][19][20] However, currently, it is unclear if the contrast between healthy tissue and tumor tissue is affected by chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…DOT can detect changes in tumor absorption within the first days after the treatment and thus could characterize breast tumor response to NAC at an earlier time than other modalities. [ 4 6 ] Previous studies [ 6 15 ] showed that DOT is a promising technique for identifying pathologic complete response (pCR) to NAC. However, the diagnostic performance of DOT varies, and it has not been subjected to multicenter studies with large samples.…”
Section: Introductionmentioning
confidence: 99%